Development of fetal nicotine and muscarinic receptors in utero - Mao,C. (2007)
The role of acetylcholine in the central and peripheral nervous systems is well established in adults. Cholinergic modulation of vascular functions and body fluid balance has been extensively studied. In the embryo-fetus, cholinergic receptors are widespread in the peripheral and central systems, including smooth muscle and the epithelial lining of the cardiovascular, digestive, and urinary systems, as well as in the brain. Fetal nicotine and muscarinic receptors develop in a pattern (e.g., amount and distribution) related to gestational periods. Cholinergic mechanisms have been found to be relatively intact and functional in the control of vascular homeostasis during fetal life in utero at least during the last third of gestation. This review focuses on the development of fetal nicotine and muscarinic receptors, and provides information indicating that central cholinergic systems are well developed in the control of fetal blood pressure and body fluid balance before birth. Therefore, the development of cholinergic systems in utero plays an important role in fetal vascular regulation, gastrointestinal motility, and urinary control.